Experimental mechanics and numerical prediction on stress relaxation and unrecoverable damage characteristics of rubber materials. (June 2021) - Leng, D.X.; Huang, C.; Xu, K.; Ma, Y.; Liu, G.J.; Li, Z.X.
Abstract: Stress relaxation and unrecoverable damage deformation are common phenomenon in rubber materials, which greatly induces instability of geometrical dimension and deteriorates the mechanical performances. The present work proposes experimental mechanics and numerical prediction for studying stress relaxation and unrecoverable damage characteristics. A time-dependent strain energy principle is established to describe the relaxation decay over time, and a quasi-plastic function is combined by considering the plastic flow criteria in order to depict the unrecoverable deformation after stress relaxation. Experimental study is conducted on multi-modes hyper-elastic mechanics and stress relaxation performances, and key parameters of the proposed constitutive model are identified by multi-island genetic algorithm (MIGA). The established constitutive equation is integrated in finite element simulation, and the numerical prediction is conducted. Combined experimental results clearly present nonlinear elastic properties, time-decay relaxation, and unrecoverable damage deformation of rubber materials. The numerical results are in good agreement with experiment ones, and the mechanism of relaxation and damage characteristics are explored. Additionally, based on the time-temperature superposition principle (TTSP) method, long-term stress relaxation behavior at low temperature is estimated by the short-term high-temperature test. This work provides efficient methods of experimental mechanics and numerical prediction for predicting the stress relaxation and damage characteristics of rubber materials, which could be also beneficial for characterizing rubber-base devices in engineering applications. Highlights: Measurements for hyper-elastic and stress relaxation of rubbers are developed. Prediction model for studying stress relaxation and unrecoverable characteristics is proposed. Mechanisms of time-decay and plastic behaviors of stress relaxation is explained.